Probing hydrogen bonding to bound dioxygen in synthetic models for heme proteins: The importance of precise geometry - Dube, Henry; Kasumaj, Besnik; Calle, Carlos; Felber, Beatrice; Saito, Alakoto; Jeschke, Gunnar; Diederich, Francois (Chemistry - A European Journal, 2009)
Distal hydrogen bonding in natural dioxygen binding proteins is crucial for the discrimination between different potential ligands such as O2 or CO. In the present study, we probe the chemical requirements for proper distal hydrogen bonding in a series of synthetic model compounds for dioxygen-binding heme proteins. The model compounds 1-Co to 7-Co bear different distal residues. The hydrogen bonding in their corresponding dioxygen adducts is directly measured by pulse EPR spectroscopy. The geometrical requirements for this interaction to take place were found to be narrow and very specific. Only two model complexes, 1-Co and 7-Co, form a hydrogen bond to bound dioxygen, which was characterized in terms of geometry and nature of the bond. The geometry and dipolar nature of this interaction in 1-Co-O2 is more similar to the one in natural cobalt myoglobin (Co-Mb), making 1-Co the best model compound in the entire series. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2020-04-02
Keywords: ENDOR spectroscopy; Heme proteins; Hydrogen bonds; Molecular recognition; Porphyrinoids